Brazilian scientific articles on “Spirituality, Religion and Health” (Archives of Clinical Psychiatry, 2016)
Abstract Background Studies on “Spirituality, religion and health” (R/S) have been increasing worldwide, including in Brazil. Mapping this production can help researchers to understand this field and also to identify gaps in the Brazilian R/S studies. Objective To analyze the Brazilian scientific articles on “Religion, Spirituality and Health” available on the main electronic databases using a bibliometric approach. Methods A comprehensive review of four major databases (PubMed, Scopus, BVS and Web of Science) was conducted. Three reviewers performed the data analysis. Off-topic articles, articles from Portugal, books and thesis were excluded. Articles were then classified by: Publication year, journal, Central focus in R/S, Academic Area, Main topic and Study Type. Results From 3,963 articles found, 686 studies were included in the final analysis (320 had central focus on R/S). There was an increase of articles in the last decade (most observational), with predominance of mental health issues, and from journals in the field of psychiatry, public health and nursing. Discussion This study enabled us to widen our understanding about how the field of “spirituality, religion and health” has been established and how this field is increasing in Brazil. These findings can help in the development of future Brazilian studies.